Towards a distributed architecture for context-aware mobile applications in UbiComp - Lopes, João; Souza, Rodrigo; Geyer, Cláudio; Costa, Cristiano; Barbosa, Jorge; Gusmão, Márcia; Davet, Patricia; Souza, Alexandre; Pernas, Ana; Yamin, Adenauer (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2013)
The applications in Ubiquitous Computing (UbiComp) environments must be aware of their contexts of interest and adapt to changes in them. Thus, a major research challenge in the area of UbiComp is related to context awareness. Considering the high distribution, heterogeneity, dynamism, and mobility of ubiquitous environments, this paper presents an architectural model for context awareness, called EXEHDA-UC (Execution Environment for Highly Distributed Applications - Ubiquitous Context awareness). The proposal includes elements to support contextual data acquisition, actuation on the environment, and processing of contextual information. We consider that the main contribution of this work is an architecture that supports the managing of the acquisition, storage, and processing of context data, in a distributed way, independently of the application, in an autonomic and rule-based perspective. To assess the functionalities of the EXEHDA-UC, we present a case study, highlighting the prototypes developed, technologies employed, and tests realized.